Differences in Students’ Creative Thinking Skills Between Those Taught Using Wordwall and Educaplay in Science Subjects - Elli; Nurhayati B.; Muhiddin Palennari; A. Mushawwir Taiyeb; Firdaus Daud (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to examine the differences in creative thinking skills among seventh-grade students taught using Wordwall and Educaplay in science learning at SMP Negeri 16 Mandai. A quasi-experimental method with a pretest-posttest non-equivalent group design was used. The sample consisted of two experimental classes: Wordwall (n = 32) and Educaplay (n = 31). Data were obtained through a creative thinking skills test and analyzed using ANCOVA. The results showed no significant difference in students’ creative thinking skills between the Wordwall and Educaplay groups (p = 0.788). This indicates that both quiz-based media had a comparable effect on students’ creative thinking performance. Although descriptive data showed improvements in posttest scores in both groups, the statistical analysis confirmed that the difference between the two media was not significant. It can be concluded that Wordwall and Educaplay are equally effective in supporting the development of students’ creative thinking skills in science learning, though neither showed superiority over the other.